2010
DOI: 10.1155/2010/943070
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Mild Stunting Show Alterations in Glucose and Insulin Metabolism

Abstract: Purpose. To evaluate glucose and insulin profiles in adolescents with mild stunting and overweight in order to assess the possibility of increased predisposition to diabetes. Subjects and Methods. The study population consisted of 66 pubertal adolescents classified as mildly stunted (height-for-age z scores ≥−2 and <−1) or of normal stature, as well as overweight (body mass index ≥85th percentile) or normal weight. Beta-cell function and insulin resistance were evaluated according to the homeostasis model asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…Because it reflects the accumulated, permanent, and long-term effects of deficiency in early childhood nutrition, stunting is widely considered the best epidemiological indicator for assessing chronic malnutrition [41]. Early life stunting has been shown to be associated with increased insulin resistance [42], altered fat metabolism [43], increased risk for chronic disease [44], impaired immune function [45], and increased risk of hypertension and cardiovascular disease [46]. Compounding these later life morbidities is the strong body of evidence consistently demonstrating the association between stunting and cognitive deficits [18, 20, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Because it reflects the accumulated, permanent, and long-term effects of deficiency in early childhood nutrition, stunting is widely considered the best epidemiological indicator for assessing chronic malnutrition [41]. Early life stunting has been shown to be associated with increased insulin resistance [42], altered fat metabolism [43], increased risk for chronic disease [44], impaired immune function [45], and increased risk of hypertension and cardiovascular disease [46]. Compounding these later life morbidities is the strong body of evidence consistently demonstrating the association between stunting and cognitive deficits [18, 20, 47].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that postnatal undernutrition during the first year of life was associated with higher 2-hour glucose and insulin levels after an oral glucose tolerance test (Gonzalez-Barranco et al, 2003). A study in adolescents from Brazil found that short height or stunting was associated with higher fasting glucose, insulin resistance, and abdominal obesity (da Luz Santos et al, 2010). Collectively, these findings lend indirect support to the hypothesis that poor net nutrition during postnatal growth and development, manifested in short legs in our study, alters regulation of physiologic mechanisms responsible for energy balance, resulting in excess adiposity and increased risk of adult diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the evidence to support the relationship between stunting and obesity emerges from some cross-sectional studies that point towards a possible risk of overweight/ obesity among stunted children (7)(8)(9)(10)(11) and adolescents (12)(13)(14) . Some studies have also shown that stunted children and adolescents have higher total body fat percentage (BF%) and central adiposity (14)(15)(16)(17)(18) .…”
mentioning
confidence: 99%
“…Some studies have also shown that stunted children and adolescents have higher total body fat percentage (BF%) and central adiposity (14)(15)(16)(17)(18) . Central adiposity has been independently associated with high levels of serum TAG, non-HDL cholesterol, fasting insulin, homeostatic model assessment of insulin resistance and C-reactive protein in young children (19,20) .…”
mentioning
confidence: 99%